State Legitimacy and Conflict Resolution in African States comparing the Bakassi Peninsula dispute between Nigeria-Cameroon and the Badme border dispute between Ethiopia-Eritrea. - Collins, Nwana Tifu. (Deutschland Lambert, 2013)
Using the Bakassi dispute between Nigeria and Cameroon, the Badme Conflict between Ethiopia and Eritrea; this book elucidates how variations in state formation processes and sources of legitimacy account for why the international community is successful in preventing or resolving conflicts in some territorial disputes but fails to do so in others. How these variations in the African state formation process affect their dependence upon the international political system for legitimacy and response to international pressure in conflict resolution. The case-study method and process tracing data analysis technique are employed to acquire empirical data and analyze the variables investigated. This book is recommended for academics in African politics and international security actors.
Includes bibliographies
Keywords: Conflict Resolution